Vascular contributions to the neurobiological effects of prenatal alcohol exposure - Sarah Z. Momin; Jacqueline T. Le; Rajesh C. Miranda (Frontiers Media S.A., 2023)
Background: Fetal alcohol spectrum disorders (FASD) are often characterized as a cluster of brain-based disabilities. Though cardiovascular effects of prenatal alcohol exposure (PAE) have been documented, the vascular deficits due to PAE are less understood, but may contribute substantially to the severity of neurobehavioral presentation and health outcomes in persons with FASD.Methods: We conducted a systematic review of research articles curated in PubMed to assess the strength of the research on vascular effects of PAE. 40 pertinent papers were selected, covering studies in both human populations and animal models.Results: Studies in human populations identified cardiac defects, and defects in vasculature, including increased tortuosity, defects in basement membranes, capillary basal hyperplasia, endarteritis, and disorganized and diminished cerebral vasculature due to PAE. Preclinical studies showed that PAE rapidly and persistently results in vasodilation of large afferent cerebral arteries, but to vasoconstriction of smaller cerebral arteries and microvasculature. Moreover, PAE continues to affect cerebral blood flow into middle-age. Human and animal studies also indicate that ocular vascular parameters may have diagnostic and predictive value. A number of intervening mechanisms were identified, including increased autophagy, inflammation and deficits in mitochondria. Studies in animals identified persistent changes in blood flow and vascular density associated with endocannabinoid, prostacyclin and nitric oxide signaling, as well as calcium mobilization.Conclusion: Although the brain has been a particular focus of studies on PAE, the cardiovascular system is equally affected. Studies in human populations, though constrained by small sample sizes, did link pathology in major blood vessels and tissue vasculature, including brain vasculature, to PAE. Animal studies highlighted molecular mechanisms that may be useful therapeutic targets. Collectively, these studies suggest that vascular pathology is a possible contributing factor to neurobehavioral and health problems across a lifespan in persons with a diagnosis of FASD. Furthermore, ocular vasculature may serve as a biomarker for neurovascular health in FASD.